Surveillance or security? the risks posed by new wiretapping technologies - Landau, Susan Eva (MIT Press, 2013)
In this book, the author argues that in embarking on an unprecedented effort to build surveillance capabilities deeply into communications infrastructure, the U.S. government is opting for short-term security and creating dangerous long-term risks. Landau describes what makes communications security hard, warrantless wiretapping and the role of electronic surveillance in the war on terror, the economic threats posed by electronic spying, and the risks created by embedding wiretapping into communications networks. How can we get communications security right? Landau offers a set of principles to govern wiretap policy that will allow us to protect our national security as well as our freedom.